New Therapy for Refractory Chronic Mechanical Low Back Pain—Restorative Neurostimulation to Activate the Lumbar Multifidus: One Year Results of a Prospective Multicenter Clinical Trial. Issue 1 (15th December 2017) - Deckers, Kristiaan; De Smedt, Kris; Mitchell, Bruce; Vivian, David; Russo, Marc; Georgius, Peter; Green, Matthew; Vieceli, John; Eldabe, Sam; Gulve, Ashish; van Buyten, Jean‐Pierre; Smet, Iris; et al.
Abstract : Objectives: The purpose of the international multicenter prospective single arm clinical trial was to evaluate restorative neurostimulation eliciting episodic contraction of the lumbar multifidus for treatment of chronic mechanical low back pain (CMLBP) in patients who have failed conventional therapy and are not candidates for surgery or spinal cord stimulation (SCS). Materials and Methods: Fifty‐three subjects were implanted with a neurostimulator (ReActiv8, Mainstay Medical Limited, Dublin, Ireland). Leads were positioned bilaterally with electrodes close to the medial branch of the L2 dorsal ramus nerve. The primary outcome measure was low back pain evaluated on a 10‐Point Numerical Rating Scale (NRS). Responders were defined as subjects with an improvement of at least the Minimal Clinically Important Difference (MCID) of ≥2‐point in low back pain NRS without a clinically meaningful increase in LBP medications at 90 days. Secondary outcome measures included Oswestry Disability Index (ODI) and Quality of Life (QoL; EQ‐5D). Results: For 53 subjects with an average duration of CLBP of 14 years and average NRS of 7 and for whom no other therapies had provided satisfactory pain relief, the responder rate was 58%. The percentage of subjects at 90 days, six months, and one year with ≥MCID improvement in single day NRS was 63%, 61%, and 57%, respectively. Percentage of subjects with ≥MCID improvement in ODI was 52%, 57%, and 60% while those with ≥MCID improvement in EQ‐5D was 88%, 82%, and 81%. There were no unanticipated adverse events (AEs) or serious AEs related to the device, procedure, or therapy. The initial surgical approach led to a risk of lead fracture, which was mitigated by a modification to the surgical approach. Conclusions: Electrical stimulation to elicit episodic lumbar multifidus contraction is a new treatment option for CMLBP. Results demonstrate clinically important, statistically significant, and lasting improvement in pain, disability, and QoL.